Analyzing Repeat Victimization - Deborah Lamm Weisel (My University, 2016)
This guide is intended as a tool to help police identify and understand patterns of repeat victimization for a range of crime and disorder problems. It describes the concept of repeat victimization and its relationship to other patterns in public safety problems, such as hot spots and repeat offenders. The guide also focuses on techniques for determining the amount of repeat victimization for specific public safety problems and how analysis of repeat victimization may be used to develop more effective responses.